2020
DOI: 10.1186/s12968-020-00683-3
|View full text |Cite|
|
Sign up to set email alerts
|

Reference ranges (“normal values”) for cardiovascular magnetic resonance (CMR) in adults and children: 2020 update

Abstract: Cardiovascular magnetic resonance (CMR) enables assessment and quantification of morphological and functional parameters of the heart, including chamber size and function, diameters of the aorta and pulmonary arteries, flow and myocardial relaxation times. Knowledge of reference ranges (“normal values”) for quantitative CMR is crucial to interpretation of results and to distinguish normal from disease. Compared to the previous version of this review published in 2015, we present updated and expanded reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
267
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 353 publications
(286 citation statements)
references
References 214 publications
(484 reference statements)
13
267
2
4
Order By: Relevance
“…However, since 2D-CMR-FT was possible in all SLV patients compared to 2D-STE and that it has become more easily available for routine CMR analyses, we believe that 2D-CMR-FT is a good alternative to 2D-STE. Furthermore, CMR reference values for LV strain values in children and adults exist and can be used for comparison [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, since 2D-CMR-FT was possible in all SLV patients compared to 2D-STE and that it has become more easily available for routine CMR analyses, we believe that 2D-CMR-FT is a good alternative to 2D-STE. Furthermore, CMR reference values for LV strain values in children and adults exist and can be used for comparison [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…By now, many studies have shown excellent feasibility and reproducibility of CMR-FT analyses tools [20][21][22] defined normal value ranges [23,24], investigated inter-vendor agreement of different available software vendors [25][26][27] and examined it in a wide range of cardiac diseases demonstrating their applicability and clinical utility (Fig. 4).…”
Section: Techniques Basic Principles and Measurement Capabilitiesmentioning
confidence: 99%
“…Quantitative cardiovascular magnetic resonance (CMR) imaging can provide a wealth of information to distinguish health from disease [ 1 ]. Four-dimensional flow (4D flow) CMR allows for a comprehensive assessment of the blood flow kinetic energy (KE) of the left ventricle (LV) [ 2 ].…”
Section: Objectivementioning
confidence: 99%